First-principles study of the matrix alloying effect of X (X = Cr, Mo, W, V, Ti, Si) on the bonding characteristics and mechanical properties of the NbC/Fe interface - Yutong Yu; Lisheng Zhong; Enci Han; Ke Shi; Kaiyuan Hu; Chengwen Zhang; Yunhua Xu; Jianhong Peng; Xu Hu (Journal of Materials Science: Materials in Engineering)
Abstract Matrix alloying is currently the most commonly used means to improve the interfacial bonding strength. To explore the influence of different alloying elements on the interfacial bonding characteristics and mechanical properties of NbC/Fe, this study investigates the influence of the alloying element X (X = Cr, Mo, W, V, Ti, Si) on the properties of the NbC/Fe surface by using first principles and analyzes the segregation behavior, work of adhesion, electronic structure, and tensile strength of the interface before and after doping with the aforementioned alloying elements. The results demonstrate that the segregation energies of Cr, V, and Ti are less than 0, indicating that these alloy elements tend to segregate at the interface. Other alloying elements have positive segregation energies and are solids dissolved in the Fe matrix. When Si is doped at the interface, the adhesion work of the interface is reduced, and the binding property of the interface is destroyed. The charge density difference and population analyses demonstrated that the charge transfer between Cr, V, Ti, Mo, and W was localized, and there was a charge depletion region, presenting covalent characteristics. After doping, the Si atom demonstrated a charge state of loss, and the charge transfer had no clear direction, indicating the characteristics of an ionic bond. According to the theoretical tensile strength analysis, the addition of Mo, W, Si, and Cu will destroy the critical tensile strain at the interface. The tensile strength and strain of the interface significantly improved after the matrix alloying of Fe by Cr, V and Ti, the microstructure evolved during the tensile deformation, and a new phase was formed. A correlation between the atomic calculations and mechanical properties can be determined using first principles, as well as a reference for practical engineering applications.